Coupled effects of static-dynamic strain rates on the mechanical and fracturing behaviors of rock-like specimens containing two unparallel fissures. (15th February 2019) - Feng, Peng; Dai, Feng; Liu, Yi; Xu, Nu-wen; Du, Hong-bo
Highlights: Conducted the coupled static-dynamic compression tests on fissured specimens. Strength and deformation characteristics highly depend on the strain rate. Observed failure modes of fissured specimens under couple static-dynamic loads. Reported the evolution of energy dissipation and release of fissured specimens. Abstract: Widely existing in various underground engineering structures, rock masses containing unparallel fissures are likely to be subjected to static pre-stress and dynamic loads simultaneously. Understanding the effects of coupled static-dynamic strain rates on the mechanical and fracturing behaviors of rocks with unparallel fissures is significant for assessing the stability of rock engineering structures. In this study, the mechanical properties and the coalescence behaviors of both intact and fissured specimens under different coupled static-dynamic loads are investigated in the laboratory, involving four static pre-stress and three strain rates. Under the same dynamic strain rate, the coupled strength and the elastic modulus of both intact and fissured specimens first increase as the static pre-stress increases up to 50% uniaxial compression strength, and then decrease. However, under the same static pre-stress, the rock-like specimens with higher dynamic strain rate are characterized by higher coupled strength and elastic modulus. In the view of energy principle, under the same static pre-stress, more energy dissipates in the loading process and releases at the end of loading under higher dynamic strain rate. Nevertheless, at the same dynamic strain rate, the highest released elastic energy occurs under the static pre-stress of 50% uniaxial compression strength. All the rock-like specimens feature the prominent tensile splitting failure through the entire specimen, and five coalescence modes of fissured specimens are summarized in the present study.